Assessing potential impact using social return on investment the case of coffee for peace in Barangay Managa, Bansalan, Davao del Sur - Picar, Marben Jan B. (2017)
Social entrepreneurship is an emerging form of business entity in the Philippines. One such social enterprise is Coffee for Peace (CFP). It is a social enterprise that is based in Davao City that introduces coffee processing to improve the lives of impoverished indigenous communities. A social enterprises are driven primarily by impact and not by profit, using traditional financial measurement tools is not sufficient in measuring the levels at which CFP achieves its objectives. Social Return on Investment analysis is more appropriate in evaluating the activities of CFP which consider other non-profit objectives. This study primarily aimed to determine the value of CFP?s intervention with its partner community, the Bagobo-Tagabawa, in Managa, Bansalan, Davao del Sur, including the factors in CFP?s enterprise that were most efficient and least efficient in creating value, and the efficiency of CFP in transforming investments into value. Based on respondents? valuation of impacts, it is estimated that CFP has a total impact value of PhP 12,448.927 for a period of five years. It was also determined that CFP can generate PhP 1.03 social impact for every PhP 1 of investment. Activities identified to be most significant were initiating a school of living tradition and employment opportunities. Least valued was the project of a recreational facility offered by a proposed coffee shop. Stakeholders were more keen to give higher value on activities where the benefits are not readily perceived. Future researchers should utilize alternative valuation methods to calculate for impacts that have no reliable proxy values. CFP should do evaluative SROI and include itself as stakeholder to determine its overall effect.